2018
DOI: 10.4103/atm.atm_344_17
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of primary and secondary restless legs syndrome among a middle-aged population in Saudi Arabia: A community-based study

Abstract: INTRODUCTION:Restless legs syndrome (RLS) is etiologically divided into primary and secondary syndromes. However, a comparative description of both types is lacking in the literature. We compared primary and secondary RLS with respect to demographic determinants, associated risk factors, and comorbidities.METHODS:Following a cross-sectional survey on the prevalence of RLS in a Saudi population, RLS cases were identified using the International RLS Study Group (IRLSSG) criteria. Cases were assessed with an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…The synthesis of reported factors associated with SDs suggested that the female sex was associated with the occurrence of insomnia disorders, nightmares, periodic limb movement disorder, and RLS; and the male sex was associated with the occurrence of OSA. The higher vulnerability of women to insomnia 5 , 94 97 and RLS 5 , 98 , 99 as compared to men is consistent with previous findings in the general population, suggesting the need to target female students when planning interventions.…”
Section: Discussionsupporting
confidence: 88%
“…The synthesis of reported factors associated with SDs suggested that the female sex was associated with the occurrence of insomnia disorders, nightmares, periodic limb movement disorder, and RLS; and the male sex was associated with the occurrence of OSA. The higher vulnerability of women to insomnia 5 , 94 97 and RLS 5 , 98 , 99 as compared to men is consistent with previous findings in the general population, suggesting the need to target female students when planning interventions.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the prevalence of RLS in the RA patients (63%) was much higher than that in the general Saudi population (8.4%) 17. This higher prevalence can be explained by the high risk of iron deficiency anemia secondary to the chronic use of NSAIDs in the RA patients,18 which was identified as the main risk factor for secondary RLS 19. Iron deficiency was further confirmed in our study population by the presence of low serum ferritin in patients with RLS.…”
Section: Discussionmentioning
confidence: 51%
“…RLS to be 30.7% among medical students in Iraq (Piro et al, 2018). Another study conducted in Saudi Arabia reported prevalence rates of primary and secondary RLS to be 64.1% and 35.9%, respectively (Alsafadi et al, 2018). Insomnia was the third commonest disorder in our study, with a prevalence rate of 36.4%.…”
Section: Discussionsupporting
confidence: 44%
“…In addition, RLS was not found to correlate significantly with unsatisfactory academic performance; this could be because secondary RLS is more severe than the primary form of this disorder (Alsafadi et al, 2018). As we excluded students suffering from other health conditions or taking medications, it is possible that our participants were more likely to have primary RLS, which therefore had less of an impact on their academic performance.…”
Section: Sleep Disordermentioning
confidence: 95%